High polyphenolic cranberry beverage alters specific fecal microbiota but not gut permeability following aspirin challenge in healthy obese adults: A randomized, double-blind, crossover trial. (December 2022) - Solch-Ottaiano, Rebecca J.; Judkins, Taylor C.; Matott, Samantha H.; McDermott, Caitlin E.; Nieves, Carmelo; Wang, Yu; Colee, James; Tagliamonte, Massimiliano S.; Dissanayake, Upuli; Mai, Volker; Percival, Susan S.; Langkamp-Henken, Bobbi
Graphical abstract: Highlights: Polyphenol-rich cranberry beverage was consumed by healthy adults who were obese. Fecal Faecalibacterium prausnitzii and Eggerthella lenta increased. Gastrointestinal permeability, inflammation, and immune function were unchanged. An intervention longer than 2 weeks may be required to observe beneficial effects. Abstract: Polyphenol-rich cranberry extracts decrease intestinal inflammation, alter gut microbiota, and decrease intestinal permeability in obese mice, but the effect has not been investigated in adults who are obese. The purpose of this randomized double-blind, cross-over feeding study in obese (BMI = 37.4 ± 1.2 kg/m 2 ) but otherwise healthy adults (n = 36) 35.4 ± 1.3 years was to determine the effects of consuming 480 mL of a high polyphenolic cranberry or control beverage daily for 2 weeks on gastrointestinal permeability, markers of inflammation and immune function, and gut microbiota. An acute aspirin challenge was administered prior to assessing intestinal permeability to determine resistance to barrier function compromise. The cranberry beverage did not affect markers of gastrointestinal permeability, inflammation, or immune function. However, fecal Faecalibacterium prausnitzii and Eggerthella lenta increased with consumption of the cranberry beverage. Data suggest that the intervention impacted bacterial communities. A longer intervention may be required to observe beneficial effects on inflammation and gastrointestinal barrier function.